Effect of isoproterenol on histamine release on rat lung mast cells (Revista Española de Fisiología, 1991)
Rat lung mast cells were stimulated with drugs with distinct mechanisms of action, namely concanavalin A, compound 48/80 ionophore A23187, in the presence of the beta adrenergic agonist (-)isoproterenol. Cells show a high response when they are stimulated with FNa-calcium. Isoproterenol does not inhibit histamine release induced by any stimuli, but enhances the response to concanavalin A and compound 48/80. Results point to the lack of beta activity on rat lung mast cells.